2021
DOI: 10.1038/s41388-021-01825-2
|View full text |Cite|
|
Sign up to set email alerts
|

SFRP2 induces a mesenchymal subtype transition by suppression of SOX2 in glioblastoma

Abstract: Intratumoral heterogeneity is a characteristic of glioblastomas that contain an intermixture of cell populations displaying different glioblastoma subtype gene expression signatures. Proportions of these populations change during tumor evolution, but the occurrence and regulation of glioblastoma subtype transition is not well described. To identify regulators of glioblastoma subtypes we utilized a combination of in vitro experiments and in silico analyses, using experimentally generated as well as publicly ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that based on its gene expression signature, cell line U-2982MG can be stratified as a mesenchymal subtype glioblastoma 19 . In contrast, cell line U-2987MG shows a proneural signature, because of high expression of the transcription factors SOX2 and PROX1 19 , 29 . Transcriptome analysis by RNAseq or gene arrays reported previously indicated that two separate groups of glioblastoma cell lines can be distinguished 19 , 25 .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous studies have shown that based on its gene expression signature, cell line U-2982MG can be stratified as a mesenchymal subtype glioblastoma 19 . In contrast, cell line U-2987MG shows a proneural signature, because of high expression of the transcription factors SOX2 and PROX1 19 , 29 . Transcriptome analysis by RNAseq or gene arrays reported previously indicated that two separate groups of glioblastoma cell lines can be distinguished 19 , 25 .…”
Section: Resultsmentioning
confidence: 94%
“…Examples of such genes are GREM1 , FN1 , LUM , SPARC , and COL1A1 30 34 . The transcription factor SOX2 has been shown to regulate glioblastoma gene expression, to shift the cells from proneural subtype to mesenchymal subtype, and SOX2 can be suppressed by SFRP2 29 . To understand more about the critical factors that are decisive for the two major glioblastoma subtypes, we used two cell lines that were produced in an earlier study: cell line U-2982MG with stable overexpression of SOX2 (U-2982MG/SOX2), and cell line U-2987MG with stable overexpression of SFRP2 (U-2987MG/SFRP2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations